Integration of Mixed Reality Technologies into the Hip Joint Arthroplasty Technique - Zubkov, O.S.; Torchynskyi , V.P. (TERRA ORTHOPAEDICA, 2024)
Summary. Background. This article is dedicated to analyzing the application of a mixed reality technology in total hip arthroplasty. The relevance of the study is determined by the increasing need to enhance the accuracy and safety of surgical interventions, which ensure the restoration of joint functions and improvement of patients’ quality of life. Objective. The study focuses on the development and clinical testing of the mixed reality-based navigation system for positioning the acetabular component of the endoprosthesis. Materials and Methods. The research includes simulation modeling and preclinical trials demonstrating significant advantages of the developed system compared to traditional methods. Results. The main findings of the study showed a significant reduction in the average and maximum deviations of implant positioning angles, indicating increased accuracy and potential ability to reduce the risk of postoperative complications. Conclusions. The research emphasizes the potential of integrating mixed reality technologies into orthopedic surgery, particularly in total hip arthroplasty procedures, contributing to the development of more efficient and safe surgical techniques.